Flint procurement and exploitation strategies in the late lower paleolithic levant : a view from Acheulo-Yabrudian Qesem Cave (Israel) - Agam, Aviad, (Archaeopress Archaeology, 2021)
This volume examines patterns of flint procurement and exploitation at the Acheulo-Yabrudian site Qesem Cave, Israel. The results show how flint had a major impact on early human decision-making and social and cultural lifeways during the Late Lower Paleolithic of the Levant.